2023
DOI: 10.1002/aesr.202300010
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Flux–Assisted Mechanism for Modest Temperature Synthesis of Large‐Grain BaZrS3 and BaHfS3 Chalcogenide Perovskites

Abstract: Chalcogenide perovskites are promising semiconductor materials with attractive optoelectronic properties and appreciable stability, making them enticing candidates for photovoltaics and related electronic applications. Traditional synthesis methods for these materials have long suffered from high‐temperature requirements of 800–1000 °C. However, the recently developed solution processing route provides a way to circumvent this. By utilizing barium thiolate and ZrH2, this method is capable of synthesizing BaZrS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…Niu et al also reported the synthesis of BaZrS 3 (and SrZrS 3 ) from BaS/SrS, Zr, and S at 600 °C with the inclusion of I 2 (60 hthough it is unclear if the reaction happens faster). We note that during the review stage of this work, Vincent et al reported a liquid flux-assisted growth mechanism for BaZrS 3 and BaHfS 3 whose results are complementary to that reported herein.…”
Section: Introductionsupporting
confidence: 88%
“…Niu et al also reported the synthesis of BaZrS 3 (and SrZrS 3 ) from BaS/SrS, Zr, and S at 600 °C with the inclusion of I 2 (60 hthough it is unclear if the reaction happens faster). We note that during the review stage of this work, Vincent et al reported a liquid flux-assisted growth mechanism for BaZrS 3 and BaHfS 3 whose results are complementary to that reported herein.…”
Section: Introductionsupporting
confidence: 88%
“…We potentially accessed a selenium rich Ag-Se binary alloy liquid flux that helped nucleate and grow large AgInSe 2 grains similar to those reported for other material systems. 39–41 The selenized film has irregularly shaped grains when selenized with regular selenization conditions, as shown in Fig. 3a and b.…”
Section: Resultsmentioning
confidence: 91%
“…So far only BaZrS 3 , [24,93,[108][109] LaYS 3 , [12,96] BaHfS 3 [110] and CaSnS 3 [111] have been realized in thin film form. New techniques such as solution processed moderate temperature synthesis using a single phase molecular precursor, [110,112] liquid flux assisted mechanism, [113] colloidal nanoscale synthesis, [114][115][116] molecular beam epitaxy [117] and post processing techniques need to be explored more for synthesis of chalcogenide perovskite. Low cost solution based techniques for deposition has to be identified in thin film making.…”
Section: Synthesis and Processingmentioning
confidence: 99%